2004
DOI: 10.1001/archderm.140.5.545
|View full text |Cite
|
Sign up to set email alerts
|

The Framingham School Nevus Study

Abstract: Objectives:To (1) describe nevus patterns using digital photography and dermoscopy; (2) evaluate the relationship between host and environmental factors and prevalence of nevi in schoolchildren; and (3) demonstrate the feasibility of conducting a longitudinal study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 37 publications
10
62
0
3
Order By: Relevance
“…Zalaudek et al [7] found that the predominance of dermoscopic types of melanocytic nevi varies according to individual’s age, and that there is a predominance of the globular pattern in children, the latter being consistent with a previous study [20]. However, there are no studies defining the most characteristic patterns in children of our population and relating particular pattern predominance with constitutional and environmental factors.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Zalaudek et al [7] found that the predominance of dermoscopic types of melanocytic nevi varies according to individual’s age, and that there is a predominance of the globular pattern in children, the latter being consistent with a previous study [20]. However, there are no studies defining the most characteristic patterns in children of our population and relating particular pattern predominance with constitutional and environmental factors.…”
Section: Introductionsupporting
confidence: 84%
“…Our aims were to investigate the number and dermoscopic patterns of melanocytic nevi among Spanish children, and to assess constitutional and environmental factors associated with the number of nevi and the dermoscopic pattern. Interestingly, there are only 2 reports in the literature regarding dermoscopic pattern prevalence in children [7, 20], and no assessment of the association of constitutional and environmental factors and dermoscopic patterns has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary findings using these data were published as an ancillary analysis in a prior study [28]. In this initial study, dermoscopic changes were noted in 10% (n = 5/50) of the study population at 1-year follow-up.…”
Section: Resultsmentioning
confidence: 83%
“…The methods have been described in detail [28]. Briefly, skin examinations and photography of back nevi were performed and follow-up skin examinations and photography were conducted 1 year later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation